High cholesterol intake modifies chylomicron metabolism in normolipidemic young men - César, Thais B. [UNESP]; Oliveira, Maria Rita M. [UNESP]; Mesquita, Carlos H.; Maranhão, Raul C. (My University, 2006)
Whether the consumption of egg yolk, which has a very high cholesterol content without excess saturated fats, has deleterious effects on lipid metabolism is controversial. Absorbed dietary cholesterol enters the bloodstream as chylomicrons, but the effects of regular consumption of large amounts of cholesterol on the metabolism of this lipoprotein have not been explored even though the accumulation of chylomicron remnants is associated with coronary artery disease (CAD). We investigated the effects of high dietary cholesterol on chylomicron metabolism in normolipidemic, healthy young men. The plasma kinetics of a chylomicron-like emulsion, doubly-labeled with 14C-cholesteryl ester ( 14C-CE) and 3H-triolein ( 3H-TG) were assessed in 25 men (17-22 y old, BMI 24.1 ± 3.4 kg/m 2). One group (n = 13) consumed 174 ± 41 mg cholesterol/d and no egg yolk. The other group (n = 12) consumed 3 whole eggs/d for a total cholesterol intake of 804 ± 40 mg/d. The nutritional composition of diets was the same for both groups, including total lipids and saturated fat, which comprised 25 and 7%, respectively, of energy intake. Serum LDL and HDL cholesterol and apoprotein B concentrations were higher in the group consuming the high-cholesterol diet (P < 0.05), but serum triacylglycerol, apo AI, and lipoprotein (a) did not differ between the 2 groups. The fractional clearance rate (FCR) of the 14C-CE emulsion, obtained by compartmental analysis, was 52% slower in the high-cholesterol than in the low-cholesterol group (P < 0.001); the 3H-TG FCR did not differ between the groups. Finally, we concluded that high cholesterol intakes increase the residence time of chylomicron remnants, as indicated by the 14C-CE kinetics, which may have undesirable effects related to the development of CAD. © 2006 American Society for Nutrition.
Keywords: Chylomicron metabolism; Dietary cholesterol; Egg yolk; Lipid emulsion; Young men; apolipoprotein A1; apolipoprotein B; cholesterol ester; chylomicron; high density lipoprotein; lipid; lipid emulsion; lipoprotein; low density lipoprotein; saturated fatty acid; triacylglycerol; triolein; adult; caloric intake; cholesterol blood level; cholesterol diet; clearance; clinical article; egg yolk; human; hyperlipidemia; lipid analysis; lipoprotein blood level; male; nutritional assessment; protein blood level; Adolescent; Adult; Apolipoprotein A-I; Apolipoproteins B; Carbon Radioisotopes; Cholesterol Esters; Cholesterol, Dietary; Cholesterol, HDL; Cholesterol, LDL; Chylomicrons; Diet; Eggs; Emulsions; Energy Intake; Humans; Isotope Labeling; Lipids; Lipoprotein(a); Male; Triglycerides; Triolein; Tritium